The Effect of Nasal Septum Deviation on The Degree of Mastoid Pneumatization - Şimşek, Tuğçe (ENT Updates, 2021)
Objective: Investigations show that nasal septum deviation changes the paranasal sinus volume on the deviation side and affects the middle ear pressure. In this study, we investigated the relationship between the degree of nasal septum deviation and the pneumatization degree of the mastoid bone air cell system. Methods: This retrospective study evaluated data collected from February 2018 to January 2020 at Amasya University Sabuncuoglu Serefeddin Training and Research Hospital The nasal deviation direction and the angle of septal deviation in coronal sections were recorded, and the mastoid bone pneumatization was classified. Then, the relationship between the nasal septum deviation and the mastoid pneumatization was evaluated. Results: There was a statistically significant difference between the rate of the right mastoid pneumatization level in relation to the direction of nasal septum deviation. Otherwise, no statistically significant differences were found in the left mastoid pneumatization between the areas to the right and left of the nasal septum deviation. Conclusion: The results showed that mastoid pneumatization significantly affected those with a deviation of the nasal septum to the right, resulting in a significant reduction in volume on the ipsilateral side. However, on the opposite side of the deviation, the mastoid pneumatization was reduced, although not as much as on the deviation side. These results suggest that nasal septum deviation may also affect mastoid pneumatization.